Sexual Dysfunction in Male Canadian Armed Forces Members and Veterans Seeking Mental Health Treatment. Issue 1 (3rd July 2019) - Richardson, J Don; Ketcheson, Felicia; King, Lisa; Forchuk, Callista A; Hunt, Renée; St. Cyr, Kate; Nazarov, Anthony; Shnaider, Philippe; McIntyre-Smith, Alexandra; Elhai, Jon D
Abstract: Introduction: There is mixed evidence regarding how posttraumatic stress disorder (PTSD) symptom clusters are associated with sexual dysfunction (SD), and most studies to date have failed to account for potentially confounding variables. Our study sought to explore the unique contribution of PTSD symptom clusters on (a) lack of sexual desire or pleasure, and (b) pain or problems during sexual intercourse, after adjusting for comorbidities and medication usage. Materials and Methods: Participants included 543 male treatment-seeking veterans and Canadian Armed Forces (CAF) personnel (aged <65 years), referred for treatment between September 2006 and September 2014. Each participant completed self-report measures of demographic variables, depressive symptom severity, chronic pain, alcohol misuse, and psychotropic medication usage as part of a standard clinical intake protocol. Hierarchical ordinal logistic regression analyses were used to determine the incremental contribution of PTSD symptom clusters on sexual dysfunction. Results: Nearly three-quarters (71.5%) of participants reported a lack of sexual desire or pleasure and 40.0% reported pain or problems during intercourse. Regression analyses suggested that avoidant/numbing symptoms were the only symptoms to be independently associated with lacking sexual desire or pleasure (AOR = 1.10; 95% CI 1.05–1.15). None of the PTSD symptom clusters were independently associated with pain or problems during intercourse. Conclusions: Sexual dysfunction is prevalent among male treatment-seeking CAF personnel and veterans. Results suggest that PTSD symptoms are differentially associated with sexual desire or pleasure concerns. Assessing sexual function among CAF personnel and veterans seeking treatment for PTSD is critical in order to treat both conditions and improve overall functioning.